PENGARUH INDEPENDENSI, PENGALAMAN DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT PADA KAP DBSD&A - Esti Damayanti, SE., M.Si.; Farah Fajriyah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This study aims to determine the influence of Independency, Experience and Professionalism Auditor on Audit Quality at public accounting firm Doli, Bambang, Sulistiyanto, Dadang & Ali. Sampling Method This research uses purposive sampling method in criteria: a. Auditors working in the Public Accounting Firm Doli, Bambang, Sulistiyanto, Dadang & Ali within a period of at least 6 months, b. Auditors have expertise in the field of audit and thoroughness in making audit reports, c. Auditor who has carried out auditing work within a period of at least 6 months. d. Auditors who have at least D3 level of education, e. Auditor who has a position equivalent partner, manager and supervisor auditing, f. Auditor working in Public Accounting Firm registered in Indonesian Institute of Certified Public Accountants Directory. Questionnaires are distributed as many as 26 questionnaires with a return rate of 17 respondents from 6 Public Accounting Firm. The data is analyzed by multiple regression method and processed with SPSS version 22 program. Data analysis is equipped with data quality test and classical assumption test.The results of this study indicate that Independence, Experience and Professionalism Auditors significantly influence audit quality. this research also shows that experience variable is the most dominant variable affecting audit quality.